Software Accessibility for Visually Impaired People: a systematic mapping study - Silveira, Barbara Cristina; Silva-de-Souza, Thiago; da Rocha, Ana Regina Cavalcanti (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
Software accessibility evaluation for visually impaired people is strongly restricted to the Web platform. Many tools are able to automatically evaluate the accessibility degree of a website according to given Web accessibility guidelines. However, these guidelines are not sufficient to objectively evaluate the accessibility of any software product, including desktop and mobile platforms. On the other hand, the ISO/IEC 25000 standards, which provide a conceptual framework for quality specification and evaluation of software products, proposes measures that while providing some guidance on how to observe and measure aspects related to accessibility are relatively abstract. In this context, this work presents a systematic mapping study that tried to identify in the technical literature the attributes and measures of software accessibility for visually impaired people, take into account that visual impairment is the most frequent among people with some type of disability. Therefore, 14 attributes and 24 measures of software accessibility were identified in seven different papers. However, some of the identified accessibility attributes have subjective characteristics, leading to inaccurate measures. Among the identified measures, the majority refers to Web page resources, which may restrict their applicability to this kind of software.